CHANGES IN CREATININE CONCENTRATION IN THE URINE OF BOXERS WHEN ADAPTING TO SPEED-STRENGTH TRAINING LOADS - Sayyora Sadullaevna Shukurova (Web of Journals Publishing, 2025)
The article presents an analysis of some biochemical changes in the process of adaptation of boxers to speed-strength training loads. A certain relationship has been established between the nature of training loads, the duration of training, physical fitness and athletic prowess of athletes as a result of creatine metabolism in conditions of high-intensity muscle activity. The information obtained allows trainers and specialists to plan training loads aimed at developing and improving the speed and strength qualities of young boxers.
Keywords: Speed-strength exercises, adaptation, load, urine creatinine boxers